Use of thyme essential oil as an antibacterial agent in raw milk intended for the production of farm cheese - Hachana, Yasser; Ghandri, Bessma; Amari, Halima; Saidi, Ismahane (Indian Journal of Dairy Science, 2019)
This study aims to use thyme essential oil (TEO) as an antibacterial agent in raw milk intended for the production of farm cheese and to test its effect on bacteriological and sensory quality. Antibacterial activity of TEO was first tested in vitro on four strains of bacteria known for their pathogenicity such as Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium and Staphylococcus aureus and then in vivo on the total mesophilic aerobic flora (TMAF) in raw milk used to produce farm cheese. All tested bacteria were very sensitive to TEO with a higher sensitivity for Escherichia coli, followed by Pseudomonas aeruginosa, then Staphylococcus aureus and finally Salmonella tiphymirium. In vivo study showed that TEO has an effective effect on TMAF of raw milk. Monitoring bacteriological quality of TEO based farm cheese during 6 days of cold storage, revealed the effectiveness of TEO on TMAF, yeasts and moulds. Despite the good bacteriological quality of TEO-based farm cheese, the strong aroma characterizing this essential oil was not well appreciated by some tasters, which had a negative impact on the final score attributed to this cheese. Thyme essential oil can be used as an alternative solution to produce healthy farm cheese without needing heat treatment, while ensuring high nutritional value food product.